MASYARAKAT PEMUJA GUNUNG SANGAKU SHINKÅŒ ; Kepercayaan terhadap Gunung bagi Masyarakat Jepang - Fajria Noviana (Universitas Dian Nuswantoro, 2008)
Mountains play some important parts in the spiritual life of Japanese society, especially for ones who live in mountain and its surroundings. Since Ancient Japan Era, mountains have come to peopleâ€™s object of worship, not only in Japan but also in the world. There are lots of facts showing the existence of mountainsâ€™ worship conducted by certain society. Mountain worship has become a part of some Japanese life which âˆ'until nowâˆ' still remains in the form of person to personâ€™s worship, as well as in religious institutions. This mountain worship phenomenon conducted by Japanese society generates problems concerning mountains to most Japanese